Investigation of Innovative Perspectives on Sports of Licensed Athletes in the Infrastructure of Clubs affiliated to the Provincial Directorate of Youth and Sports - Barış Karataş; Abdullah Yavuz Akinci (Universitas Majalengka, 2022)
In this study, it is aimed to examine the sports innovation perceptions of licensed athletes in various categories in the infrastructure of sports clubs affiliated to the Provincial Directorates of Youth and Sports, according to some variables. 145 athletes selected by simple random method from 609 licensed athletes in sports clubs affiliated to Provincial Directorates of Youth and Sports in Isparta province participated in the research. Personal information form and Innovation in Sports Scale were used as data collection tools in the research. The personal information of the participants, the scores obtained from the scale and factor scores, frequency (f) and percentage (%) values were determined. In order to determine whether the scores obtained by the athletes from the Innovation in Sports Scale differ according to the independent variables, the T test was applied to independent groups in pairwise comparisons, One-way anova was used to compare three or more variables, and the Bonferroni test was used to determine the difference between groups. In the study, the averages of the Sports Innovation Scale according to age groups, educational status, category, monthly income of the family, the state of hearing the concepts of innovation, innovative, the club's status of providing projects or trainings related to innovation in sports, evaluate the club's view of innovation, innovative perspective performance in sports and analysis were made to determine whether the difference between these averages is significant. As a result, it has been determined that the total score of the Innovation in Sports Scale and its sub-dimensions are above the average.